Perbandingan Analisis Data Curah Hujan Yang Hilang Menggunakan Metode Reciprocal, Normal Ratio , Dan Rata-Rata Aljabar (Studi Kasus : Curah Hujan Beberapa Stasiun Hujan Daerah Pringsewu) - hasyimzoem, Edwin Faisol; Zakaria, Ahmad; Sumharni, Sumiharni (Universitas Lampung, 2019)
Rainfall data is one of the data which plays an important role in order to calculate construction project, especially for flood hazard zone nor near the river zone and coastal area. In rainfall data recording sometimes an unwanted thing happened like a rainfall data vacancy in certain area, this is certainly has an impact on the construction’s calculation. On a missing rainfall data, predictions can be made using the method of reciprocal, normal ratio, an algebraic average. The purpose of this sudy is to determine the correlation value from the result of rainfall data predictions by comparing the correlation values of these three methods by using three stations R002,006,R018 in pringsewu regency. This study also aims to determine the fluctuations in the results of these three methods, which methods produces the best correlation and not too fluctuating in order to replace the missing rainfall data. The results of this research that has been done, using the method of reciprocal obtained that standard deviation give the best result among other I 0,22 which is categorized as poor value and the result of correlation average is 0,36 which is categorized as good enough. This result is the best value among the other methods which is calculated using data per years for 34 years.Keywords: algebraic average method, reciprocal method, normal ratio method, missing rainfall data, pearson correlation, standard deviation.